Assessment of Antibiotic Resistance of Escherichia coli Isolated from Poultry Droppings in the Kathmandu Valley (Tribhuvan University Journal of Microbiology, 2025)
Objective: To assess antibiotic resistance in Escherichia coli isolated from chicken droppings from selected poultry farms within Kathmandu valley.Methods: Stool samples of chicken from 21 different farms were collected aseptically and transported to Central Department of Microbiology laboratory. Samples were cultured in MacConkey and M-Endo agar to isolate E. coli and was confirmed phenotypically using biochemical tests.  The isolates were tested for antimicrobial susceptibility by modified Kirby-Bauer disk diffusion method following CLSI guidelines.Results: E. coli were isolated from all 104 dropping samples. E. coli isolates were resistant to ampicillin/sulbactam (91.34%), cefoxitin (98.07%), chloramphenicol (77.88%), ciprofloxacin (83.65%), contrimoxazole (79.81%), gentamicin (65.38%), levofloxacin (83.65%), and tetracycline (100%). While less proportions of E. coli were resistant to ceftriaxone (16.35%), colistin (3.85%) and imipenem (25%). Out of 104 isolates, 94 (90.38%) were multidrug resistant (MDR).  Frequency of cleaning of the coop (p = 0.0017), farm size (p